FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG ECERAN DI DESA PUNCAK KECAMATAN PULUBALA KABUPATEN GORONTALO - Paramata, Sri Hantuti; Yusuf, Siska (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2024)
This research aims to find out what factors influence the income of retail dealer in Puncak Village, Pulubala District, Gorontalo Regency. This research used quantitative research approach with a questionnaire research instrument. The data source used 30 respondents. Factors are influence retail dealer’s income (Y) and factors are influence it consist of X1 = Education, X2 = Capital, X3 = Working hours, and X4 Type of goods. The analytical tool used is multiple linear regression. The results of the analysis concluded simultaneously the factors X1 = education, X2 = capital, X3 = working hours, and X4 type of goods have a significant effect on retail dealers' income. As shown by RSquare 7.8 percent